ESTIMASI KEBUTUHAN MATERIAL PADA PROSES FABRIKASI KAPAL TONGKANG 230x80x16 FEET BERDASARKAN SWC - Dani, Ahmad; Hilmy, Zakwan; Susilo, Trisno; Tyas Adi, Fajar (JURNAL JALASENA, 2024)
The Riau archipelago province has quite a large sea area and therefore the development of water transportation technology, namely ships, is a quite promising business field in the ship construction industry in Indonesia. The aim of this research is to calculate the weight of materials and make plans to estimate material needs, where Calculating ship weight and planning ship material estimates using CAD (Computer Aided Design) and Excel applications. It is hoped that from the research results, calculating ship weight and estimating material requirements will be able to achieve efficiency and effectiveness in ship production for the company. The calculation results obtained an estimated material requirement of 987,592 tons in the shipbuilding of 230x80x16 feet barge based on swc.